Intrinsically Stretchable Organic Electrochemical Transistors with Rigid‐Device‐Benchmarkable Performance (Adv. Sci. 29/2022). Issue 29 (14th October 2022) - Liu, Dingyao; Tian, Xinyu; Bai, Jing; Wang, Yan; Cheng, Yixun; Ning, Weijie; Chan, Paddy K. L.; Wu, Kai; Sun, Junqi; Zhang, Shiming
Abstract : Stretchable Organic Electrochemical Transistors Stretchable organic electrochemical transistors (OECTs) provide a promising solution to develop the next‐generation soft brain probes for a more reliable brain‐machine interfacing. In article number 2203418, Shiming Zhang and co‐workers introduce a universal approach to boost the performance of stretchable OECTs by controlling the oxygen‐permeability of the elastic substrates. The resultant devices show comparable performance with their rigid counterparts.